Perlindungan Hukum Peserta Rapat Umum Pemegang Saham dalam Risalah di Bawah Tangan - Adib Al Ichsan (Lex Renaissance, 2017)
This research raises the issues of, first, the legal protection of the interests of GMS participants in Law No. 40 of 2007 concerning Limited Liability Companies, and second, the strength of evidence of GMS minutes of meeting prepared in the form of original deed. This study is library research using a normative juridical approach. Based on the results, we conclude that, first, the legal protection for participants in a General Meeting of Shareholders (GMS) has been arranged in detail in the Law on Limited Liability Companies. The resolution of GMS can be prepared as a notarial deed or minutes of meeting in the form of original deed. Second, the strength of evidence of GMS original deed is deemed perfect as a proof of evidence even though it is based on minutes of meeting or private deed. The minutes are then set forth in the form of a Private Deed Resolution. It is an authentic deed because it fulfills the elements of an authentic deed and does not conflict with the laws and regulations.